2014
DOI: 10.1002/2012wr013289
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic downscaling of precipitation to high-resolution scenarios in orographically complex regions: 1. Model evaluation

Abstract: [1] The simulation of space-time precipitation has been studied since the late 1980s. However, there are still many open issues concerning the most appropriate approach to simulate it, specially in highly heterogeneous areas, such as in mountain environments. For this reason, we present here a comprehensive investigation of the Space-Time NeymanScott Rectangular Pulses model, with the purpose of analyzing its performance in a challenging Alpine environment of Switzerland and identifying weaknesses that can dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…In particular, mathematical modeling of hydrological data as a stochastic process is of interest to a variety of hydrological areas such as flood forecasting, reservoir operations and agricultural planning [61][62][63]. Current state-of-the-art stochastic precipitation models at a single site or for multiple sites can reproduce a wide range of statistics from hourly scale extremes to larger aggregation periods [64][65][66][67][68][69][70][71][72][73][74][75]. In particular, numerous approaches for the stochastic modeling of daily rainfall data are available in the hydrological and climatological literature [76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mathematical modeling of hydrological data as a stochastic process is of interest to a variety of hydrological areas such as flood forecasting, reservoir operations and agricultural planning [61][62][63]. Current state-of-the-art stochastic precipitation models at a single site or for multiple sites can reproduce a wide range of statistics from hourly scale extremes to larger aggregation periods [64][65][66][67][68][69][70][71][72][73][74][75]. In particular, numerous approaches for the stochastic modeling of daily rainfall data are available in the hydrological and climatological literature [76][77][78][79][80][81][82][83][84].…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall generators exist for both single site and spatial applications and three main categories of rainfall generators can be recognized (Bordoy and Burlando 2014). The first category is the one of the Markovian models, in which rainfall occurrence and rainfall amount are modelled separately in a two-step approach (Wilks 1998;Mehrotra et al 2006;Kim et al 2008;Wilks 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Given their formulation, the models are not expected to exhibit scaling behaviour (e.g., Marani 2003). However, Olsson and Burlando (2002), Bordoy and Burlando (2014) empirically demonstrated that a NSRP model can well reproduce rainfall properties at different timescales, applying both its single site (20 min-1 week) and spatial-temporal configuration (1 h-45 days). Another advantage of this type of models is the possibility to include third-order moments in the simulation algorithm to better model extremes (Burton et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations